Forest set-aside policy for International biodiversity targets? Obstructive bureaucratic territoriality in Germany and Sweden. (1st December 2021) - Logmani-Aßmann, J.; Lindahl, K. Beland; Krott, M.; Burns, S.L.; Giessen, L.
Under the auspices of the Convention on Biological Diversity, the Aichi Biodiversity Target 11 requires setting aside vast currently managed areas for conservation purposes. Following bureaucratic politics theory, forestry and environmental domestic bureaucracies use these international targets in their struggle for power and territoriality over forested areas. Against this background, this study aims to analyze the resulting politics on setting aside forest areas from active forest management in Germany and Sweden. Employing a qualitative case study design and empirical data from policy documents and key informant interviews, our results indicate that bureaucracies prioritize instruments that are well aligned with their formal objectives, the interests of their informal constituencies, and their territorial interests. Such struggles dominate the development of policy instruments in both countries obstructing political compromise which results in a logjam in the development of substantial forest set-aside policy. We conclude that unless domestic politics and key bureaucracies provide conducive political conditions international commitments will be very difficult to achieve, even if they are formulated into clearly measurable international targets.